The influencing factors of cognitive impairment in elderly individuals in Chengdu city: a cross-sectional study based on AD8 - Xi Ruan; Hongyi Li; Ziqi Wang; Yu Wang; Yamei Nie; Yan Li; Yuanjing Li; Qin Fan; Baiwei Ni; Yinxue Huang; Xuan Hong; Ting Sun; et al. (BMC Geriatrics)
Abstract Background With the aging of society, cognitive impairment in elderly people is becoming increasingly common and has caused major public health problems. The screening of cognitive impairment in elderly people and its related influencing factors can aid in the development of relevant intervention and improvement strategies. Methods In this study, stratified random cluster sampling was used to conduct a cross-sectional survey of elderly individuals aged 65 years in Chengdu, Sichuan Province, through an electronic questionnaire from November 2022 to November 2023. Descriptive analysis and logistic regression analysis were used to investigate cognitive impairment and its relevant influencing factors. Results Among the 16,609 elderly people, 7524 (45.3%) were males and 9085 (54.7%) were females, with an average age of 73.6 ± 6.5 years (age range 65–101 years). The average years of education was 5.9 ± 6.2 years, and the proportion of individuals with cognitive impairment was 13.1%. With increasing age, the risk of cognitive impairment increased significantly. The risk factors for cognitive impairment in elderly individuals included advanced age, hypertension, heart disease, diabetes, cerebrovascular disease, depressive symptoms, and anxiety symptoms, while the protective factors included higher education level, married status, and greater life satisfaction. Conclusion Cognitive impairment in elderly individuals in Chengdu is serious. We can intervene in and improve cognitive impairment in elderly people by controlling blood pressure and blood sugar, treating depressive and anxiety symptoms and developing community colleges for elderly people and increasing satisfaction with life.